ANALISIS DETERMINAN STRATEGI BISNIS DAN IMPLIKASI TERHADAP PENGEMBANGAN BISNIS LEAN CANVAS DENGAN KONSEP GE-MCKINSEY DAN BEST WORST METHOD(STUDI KASUS DI UMKM DAPUR MACHO) - Ahmad Dzaki, (2022)
The impact of Covid-19 has affected many UMKM in Indonesia. One of them is the Dapur Macho UMKM which is a UMKM in the culinary field with most of its customer segments from housewives. The impact felt by Dapur Macho UMKM in the last year is a decrease in the number of customers and sales levels by 7% from June 2021 to January 2022. In this study, 4 stages were carried out, the first stage was to analyze internal and external factors based on the results of interviews conducted with business owners. Then the second stage was carried out by analyzing the GE (General Electric) - Mckinsey matrix with weight and rating assessments obtained from Macho Kitchen UMKM experts, namely CEO, Admin, and Chef. The results of the GE-Mckinsey Matrix analysis were obtained from the total score results on the Competitive Strength variable of 3,317 and the Industry Attractiveness variable of 2,896 with the position obtained being in the selectively / Manage for earnings position. The third stage of the calculation was carried out using the BWM (Best Worst Method) method based on the results of a comparative survey of criteria with many respondents as many as 88 respondents. The results obtained in the BWM calculation are a reliability value (Ksi) of 0.089, then the selected criteria are "There is a more attractive offer by competitors" with a weight value of 0.323. The last stage is to provide a strategy proposal, namely "Increasing product value and developing promotional concepts by utilizing digital platforms", then the strategy will later be implied into several elements of the strategy in Lean Canvas.